2019
DOI: 10.1016/j.jad.2019.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood trauma alters neurological responses to mental stress in patients with coronary artery disease

Abstract: Background: Early childhood trauma is known to independently increase adverse outcome risk in coronary artery disease (CAD) patients, although the neurological correlates are not well understood. The purpose of this study was to examine whether early childhood trauma alters neural responses to acute mental stress in CAD patients. Methods: Participants (n = 152) with CAD underwent brain imaging with High Resolution Positron Emission Tomography and radiolabeled water during control (verbal counting, neutral spea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 94 publications
(123 reference statements)
1
14
0
Order By: Relevance
“…We also found that CVD patients with mental stress-induced myocardial ischemia had increased anterior cingulate function with mental stress compared to CVD patients without ischemia [41], and brain activation in these regions correlated with increased stress-induced peripheral vasoconstriction [27]. Furthermore, in a series of studies, we observed that CVD patients have differing brain activation patterns to mental stress based on gender [55], obesity [56], symptoms of angina [42,57], history of early trauma [58], and co-occurring depression [59,60].…”
Section: Neurobiology Of Stress In Relation To Cvdsupporting
confidence: 50%
“…We also found that CVD patients with mental stress-induced myocardial ischemia had increased anterior cingulate function with mental stress compared to CVD patients without ischemia [41], and brain activation in these regions correlated with increased stress-induced peripheral vasoconstriction [27]. Furthermore, in a series of studies, we observed that CVD patients have differing brain activation patterns to mental stress based on gender [55], obesity [56], symptoms of angina [42,57], history of early trauma [58], and co-occurring depression [59,60].…”
Section: Neurobiology Of Stress In Relation To Cvdsupporting
confidence: 50%
“…Through its connections with the parietal lobe, the inferior lobe also mediates a heightened activity in brain areas involved in perception and cognition during stress. We have recently shown that among individuals with CAD, this region is highly activated in response to acute MS [ 11 ], and the magnitude of activation correlates with both the peripheral vasoconstriction and MS-induced myocardial ischemia [ 21, 22, 27 ]. Our current findings further expand the role of inferior frontal lobe activation with respect to cardiovascular health by demonstrating that higher activation of this region adversely affects executive function, at least partly by a greater vasoconstrictor response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of HR-PET images, including realigning, normalizing, and smoothing, was completed following established protocols using statistical parametric mapping (SPM12; www.fil.ion.ucl.ac.uk/spm/ software/spm12/) [35][36][37]. First, a mean intensity image was created from the eight individual scans.…”
Section: Brain Imaging Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Traumatic events during childhood are a well-known risk factor for FMS that also has the potential to alter brain activation patterns [70]. Cognitive coping mechanisms including reappraisal were identified to contribute to resilience in children with a history of maltreatment.…”
Section: Discussionmentioning
confidence: 99%